A mobile application for personal colour analysis - Hye Rim Hong; Young In Kim (Cogent Business & Management, 2019)
This study developed a mobile app of the personal colour analysis system, which determines the clothing colours that are harmonized to a user's personal skin and hair colouring. The mobile application is easy and accurate for non-experts to use, and it employs photographs of a user's skin and hair colours to automatically calculate and categorize personal colouring instead of using fabrics as an analysing material. The application applies virtual packets of fabric swatches to virtual tee shirts and overlays them on the user's photographs to obtain a personal colour analysis. Through this process, the application reduces personal time and cost dramatically, and it allows users to analyse their personal colours repeatedly by themselves. This study is expected to establish a framework to advance research on clothing colours. The application is also expected to substantively assist consumers in choosing clothing colours.
Keywords: 650; colour matching; mobile application; personal colour analysis